2010
DOI: 10.1007/s12028-010-9475-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Hypertonic Saline and Mannitol on Whole Blood Coagulation In Vitro Assessed by Thromboelastometry

Abstract: Blood coagulation is disturbed more by 15% mannitol than by equiosmolar 2.5% saline. This disturbance seems to be attributed to overall clot formation and strength but also to pure fibrin clot firmness. This saline solution might be more favorable than mannitol before craniotomy in patients with a high risk of bleeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
21
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 24 publications
7
21
0
Order By: Relevance
“…Similar to our study, Luostarinen et al (1) showed that HS is more problematic than mannitol with respect to coagulation. This study also showed that the use of 3% HS could be a better choice in patients with abnormal bleeding tendency and/or patients who are under a high risk of bleeding surgery.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Similar to our study, Luostarinen et al (1) showed that HS is more problematic than mannitol with respect to coagulation. This study also showed that the use of 3% HS could be a better choice in patients with abnormal bleeding tendency and/or patients who are under a high risk of bleeding surgery.…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, adding HES to this fluid severely increased the negative impact on the extrinsic coagulation pathway by increasing hemodilution. In previous studies, no InTEM analysis has been performed but data gained using ExTEM analysis were similar to that in the present study (1,6,13). We found disruption of platelet function only when mannitol or HS was combined with HES solution.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In both cases, induced disorders are mainly dependent on fibrinogen-fibrin interactions as demonstrated by ROTEM®. The results are consistent with those of previously published studies (12)(13)(14), although the new contribution is the combination of both osmotic solutions with starch currently used in current practice.…”
supporting
confidence: 92%